Leibniz, la Ciencia y el Código Civil - Escobar Rozas, Freddy (Pontificia Universidad Católica del Perú, 2015)
Yhis article addresses the issue about the differences between the old regulatory bodies and the current Civil Codes. t he author analyzes from the Medieval Period until the present to evidence the change and evolution that made the thinkers to apply the geometric method to Law and how to configure the rules in the Civil Law. Furthermore, it recognizes and analyzes the contributions of e uropean writers and thinkers that promoted the Scientific Revolution of the 17th century, especially the work of the lawyer Gottfried Wilhelm Leibniz.

El presente artículo aborda la temática sobre las diferencias entre los cuerpos normativos antiguos y los Códigos Civiles actuales. El autor realiza un análisis desde la época Medieval hasta la actualidad para evidenciar el cambio y la evolución que hicieron los pensadores para aplicar el método geométrico al Derecho y la forma de configurar de las normas en el Civil Law. Asimismo, se reconoce y analiza los aportes de los escritores y pensadores europeos, que impulsaron la Revolución Científica del siglo XVII, en especial la obra del abogado Gottfried Wilhelm Leibniz.
Leibniz, the Science and the Civil Code
Keywords: Scientific Revolution; Leibniz; Geometry; Descartes; Reasoning; Logical-Deductive; Revolución Científica; Leibniz; Geometría; Descartes; Razonamiento; Lógico-Deductivo; https://purl.org/pe-repo/ocde/ford#5.05.00